Metabolic and Histological Effects of Different Polyunsaturated Fat Types in the Diet: Omega-3 and Omega-6 - Daghestani, Maha Hasan; Virk, Promy; EL-Kenawy, Ayman EL-Meghawry (Pakistan Journal of Nutrition, 2012)
The beneficial effects of polyunsaturated fats and omega 3 supplements in human and animal nutrition have been widely discussed and established though clinical and experimental studies. In this study the High-Fat (HF) diet rodent models were used to evaluate the effects high doses of two polyunsaturated fats omega-3 and omega-6 on metabolic parameters and histology of liver and kidney. Male and female Wistar rats were fed High-Fat (HF) diets containing Omega-3 fish oil supplements (HF-F) and Omega-6 corn oil (HF-C) at a level that was equivalent to three times the maximum safe daily dosage and the control group was fed with regular laboratory chow. Body weight and plasma parameters of glucose, cholesterol and triglycerides were measured after a 8 week diet course. Rats fed both the high fat oil based diets (HF-F, HF-C) reported a significantly higher body weight gain than the control group. Plasma triglyceride levels were significantly higher in the high fat diets being highest in the fish oil based diet. Both the high fat diets fed animals (HF-F, HF-C) showed pronounced hepatic micro vesicular steaosis and renal interstitial inflammation in comparison with the control in the histological studies. Thus this study demonstrated that high fat diets with polyunsaturated fats including omega-3 rich fish oil could induce dyslipidemia and obesity in rodent models reflecting signs of metabolic syndrome in the humans.